Tendering strategies for infrastructure works at Plot 8MD3, Precinct 8, Putrajaya / Nur Syazwana Sanaidi - Sanaidi, Nur Syazwana (Universiti Teknologi MARA UiTM,Perak, 2022)
Tendering is the process of inviting bids from interested contractors to complete the construction projects. Contractor’s quantity surveyor will be responsible in pricing of construction work, dealing with all issues which relating to costs and values of the project. Thus, this report will briefly clarify the strategy in tendering for supplying labour, machineries and materials for all drainage works, sewerage works, and water reticulation works as per latest construction drawing and materials specifications at the plot 8MD3, Precint 8, Putrajaya, Wilayah Persekutuan Putrajaya. Strategy in tendering is very important to ensure the company receive the letter award of the tender project among the competitive construction company. The objective of this report is to investigate the fluctuation of price item where may can be affecting the strategy of tendering or when pricing the tender. Observation through getting the quotation of the material from supplier can be one of the main points for quantity surveyor observe the fluctuation of price. By having the strategy, it can improve the skill in work, affirms an organization’s mission and values, gives a future vision and established goals.